2014
DOI: 10.1016/j.vaccine.2013.06.098
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a reported history of chickenpox in targeting varicella vaccination at susceptible adolescents in England

Abstract: HighlightsChickenpox history may enable cost-effective vaccination of susceptible individuals.We tested the validity of reported chickenpox history in adolescents.Vaccine would be wasted in most adolescents with a negative or uncertain history.6–9% of those with a positive chickenpox history would remain susceptible.These data are needed to inform cost-effectiveness of proposed vaccine programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Although parental report of varicella history has been shown to be reliable for young children, history of varicella as reported by parents/guardians or the subject may be less reliable in adolescents, and for younger children as varicella becomes less common. 27,28 The accuracy of a report of varicella in the past year may also be subject to recall bias, especially if the case of varicella occurred earlier in that time period. In addition, as varicella disease has become rare and much milder in the vaccine era, parents may have been less able over time to accurately recognize a varicella case.…”
Section: Figurementioning
confidence: 99%
“…Although parental report of varicella history has been shown to be reliable for young children, history of varicella as reported by parents/guardians or the subject may be less reliable in adolescents, and for younger children as varicella becomes less common. 27,28 The accuracy of a report of varicella in the past year may also be subject to recall bias, especially if the case of varicella occurred earlier in that time period. In addition, as varicella disease has become rare and much milder in the vaccine era, parents may have been less able over time to accurately recognize a varicella case.…”
Section: Figurementioning
confidence: 99%
“…22 A study of U.K. adolescents found that self-reported history of chickenpox was a good predictor of seropositivity, although report of not having or equivocal history of chickenpox was not a good predictor of seronegativity. 23 The prevalences of eczema observed in the NHIS are lower than the prevalences observed in the National Survey of Children's Health 2003-04 4 and 2007-08. 5 This may be due to differences in the sampling methodology.…”
Section: Discussionmentioning
confidence: 79%
“…Self‐reported history of having or not having chickenpox infection was previously studied in pregnant women in the U.S. and found to discriminate well between seropositivity and seronegativity . A study of U.K. adolescents found that self‐reported history of chickenpox was a good predictor of seropositivity, although report of not having or equivocal history of chickenpox was not a good predictor of seronegativity . The prevalences of eczema observed in the NHIS are lower than the prevalences observed in the National Survey of Children's Health 2003–04 and 2007–08 .…”
Section: Discussionmentioning
confidence: 99%
“…By 16 years of age, 90% of the UK population will have serological evidence of exposure [14]. Infection may be subclinical and unrecognized by the individual: in adolescents with a negative or uncertain history of chickenpox, 67% and 84% show immunity respectively [15].…”
Section: Epidemiology Of Infection and Immunitymentioning
confidence: 99%